Art power - Groys, Boris (Cambridge, Mass. : MIT Press, 2008)
Logic of equal aesthetic rights ##- On the new ##- On the curatorship ##- Art in the age of biopolitics: from artwork to art documentation ##- Iconoclasm as artistic device: iconoclastic strategies in film ##- From image to image file##- and back: art in the age of digitalization ##- Multiple authorship ##- The city in the age of touristic reproduction ##- Critical reflections ##- Art at war ##- The heros body: Adolf Hitler's art theory ##- Educating the masses: socialist realist art ##- Beyond diversity: cultural studies and its post-Communist other ##- Privatizations, or artificial paradises of post-Communism ##- Europe and its others.
Includes bibliographical references (p. [183]-[190]).
boek